Shared Leadership and Improvisation: Dual Perspective of Cognition-Affection - Dixuan Zhang; Xiaohong Wang; Shaopeng Zhang (Behavioral Sciences, 2023)
Improvisation is an effective way to cope with rapid changes and obtain unexpected opportunities in a complex environment. Based on the cognitive-affective system theory, this study investigates the dual mediating role of cognitive flexibility and emotional intelligence between shared leadership and improvisation and the moderating role of promotion focus. We used multilevel and multi-sourced data to test the theoretical model and used a social network approach to measure shared leadership in teams. Our sample was comprised of 40 teams and 240 team members. The empirical findings indicated that cognitive flexibility and emotional intelligence mediated the relationship between shared leadership and improvisation; promotion focus moderated the relationship between shared leadership and improvisation, and the mediation effect via cognitive flexibility. This study contributes to expanding on improvisation research from the perspective of shared leadership and incorporating both the cognitive and the emotional process of the generation of improvisation into a theoretical framework from a compound perspective, which will open the black box for the mediation mechanism from shared leadership to improvisation. Furthermore, promotion focus is introduced into the research and creatively corresponds to the cognition-affection mediation mechanism, which expands the applicable scope of the regulatory focus theory.